2018
DOI: 10.1128/mbio.02325-17
|View full text |Cite|
|
Sign up to set email alerts
|

Role of Severe Acute Respiratory Syndrome Coronavirus Viroporins E, 3a, and 8a in Replication and Pathogenesis

Abstract: Viroporins are viral proteins with ion channel (IC) activity that play an important role in several processes, including virus replication and pathogenesis. While many coronaviruses (CoVs) encode two viroporins, severe acute respiratory syndrome CoV (SARS-CoV) encodes three: proteins 3a, E, and 8a. Additionally, proteins 3a and E have a PDZ-binding motif (PBM), which can potentially bind over 400 cellular proteins which contain a PDZ domain, making them potentially important for the control of cell function. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
347
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(371 citation statements)
references
References 80 publications
(137 reference statements)
8
347
1
4
Order By: Relevance
“…activity (Surya et al, 2015;Verdia-Baguena et al, 2013). In addition, some accessory proteins of CoVs, such as SARS-CoV 3a and 8a, the human coronavirus 229E (HCoV-229E) 4a protein and the porcine epidemic diarrhea virus (PEDV) ORF3, have been identified as viroporins (Castano-Rodriguez et al, 2018;Wang et al, 2012;Zhang et al, 2014). PDCoV also encodes an E protein and three accessory proteins (NS6, NS7 and NS7a) (Fang et al, , 2017.…”
Section: Discussionmentioning
confidence: 99%
“…activity (Surya et al, 2015;Verdia-Baguena et al, 2013). In addition, some accessory proteins of CoVs, such as SARS-CoV 3a and 8a, the human coronavirus 229E (HCoV-229E) 4a protein and the porcine epidemic diarrhea virus (PEDV) ORF3, have been identified as viroporins (Castano-Rodriguez et al, 2018;Wang et al, 2012;Zhang et al, 2014). PDCoV also encodes an E protein and three accessory proteins (NS6, NS7 and NS7a) (Fang et al, , 2017.…”
Section: Discussionmentioning
confidence: 99%
“…They could possibly be responsible for inflammasome activation [49,96]. It was recently shown that the SARS 3a protein activates the NLRP3 inflammasome in lipopolysaccharide-primed macrophages by affecting K + efflux and mitochondrial reactive oxygen species [93].…”
Section: Coronavirus: E and 3a Viroporinsmentioning
confidence: 99%
“…[259] By binding to the E6AP ubiquitin ligase, HPV E6 targets p53 and the PDZ domain proteins for degradation (Figure 12a). [265] In Kaposi's sarcoma herpesvirus, expression of the PDZ-LIM domain-containing protein 2 gene (PDLIM2) is repressed, which enables tumorigenesis and tumor maintenance in infected cells. While HPV protein E6 has been shown to interact with p53 and E6AP in both low and high-risk HPVs, [260,261] only the high-risk cancer-causing HPV E6 proteins contain a C-terminal PDZ binding motif, which is recognized by different PDZ domain proteins depending on the HPV strain.…”
Section: Targeting Pdz Domain Proteins Involved In Viral Infectionsmentioning
confidence: 99%